TheChallenger launch decision: case and teaching note - Liedtka, Jeanne (International journal of value-based management, 1990)
The following is a brief reconstruction of the major events preceding the launch of the Space Shuttle Challengeron January 28th, 1986, based upon testimony offered at the hearings of the Presidential Commission (1986).